A LITERATURE REVIEW: THE IMPACT OF PHARMACIST COUNSELING ON MEDICATION ADHERENCE IN TYPE 2 DIABETES MELLITUS OUTPATIENTS - Sulaeman, Agus; Vallini, Lia (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic disease with a high prevalence that requires long-term therapeutic management. One of the biggest challenges in managing T2DM is the low level of patient adherence to medication, which can trigger serious complications and increase the economic burden on the healthcare system. Pharmacist counseling plays an important role in improving patient adherence through education, motivation, and support. This study aimed to analyze the effect of pharmacist counseling on medication adherence in T2DM outpatients using data from scientific journals published between 2019 and 2024, sourced from PubMed, ScienceDirect, and Google Scholar. A total of 10 articles were reviewed and selected based on the following inclusion criteria: studies focusing on pharmacist counseling and medication adherence in T2DM outpatients, published in English or Indonesian, and accessible in full text. The study found that various counseling interventions, such as face-to-face education, reminders via short message (SMS), and the use of informational guidance, significantly improved patient adherence, as measured by clinical parameters such as decreased HbA1c levels and improved quality of life. These findings suggest that pharmacist counseling can be an effective approach to improve the success of T2DM therapy while having a positive impact on patients' quality of life. Keywords: Diabetes mellitus, pharmacist counseling, patient compliance, HbA1c, Quality of life, pharmacy education.